Myxomycete with the ability to accumulate heavy metals. Fuligo septica - Kryvomaz, Т. І.; Minter, D. W.; Michaud, A. (CABI, 2019)
Diagnostic features. Large conspicuous irregular yellow or white plasmodia and aethalia; spores <10 µm diam.; cortex rough, not persistent; Mucilago crustaea P. Micheli ex F.H. Wigg., a common lookalike species found in similar habitats, is sometimes misidentified as F. septica, but its thickened cortex has crystalline, not granular, calcium carbonate.
Keywords: myxomycetes; міксоміцети; Fuligo septica